The effect of LyPRP/collagen composite hydrogel on osteogenic differentiation of rBMSCs - Chen, Manyu (Regen Biomater, 2020)
Although platelet-rich plasma (PRP) plays a significant role in the orthopedic clinical application, it still faces two major problems, namely, uncontrollable factors release, frequent preparation and extraction processes as well as the inconvenient form of usage. To overcome these shortcomings, freeze-dried PRP (LyPRP) was encapsulated into bioactive Col I hydrogel to induce osteogenic differentiation of rabbit bone marrow mesenchymal stem cells (rBMSCs). And PRP/Col І composite hydrogel was prepared as a control. Compared with Col І hydrogel, the introduction of platelets significantly improved the mechanical properties of hydrogels. Meanwhile, platelets were evenly distributed in the composite hydrogels network. The sustainable release of related factors in the composite hydrogels could last for more than 14 days to maintain its long-term biological activity. Further cell experiments confirmed that PRP and LyPRP could effectively alleviate the contraction of collagen hydrogel in vitro, and promote the adhesion, proliferation and osteogenesis differentiation of rBMSCs. The results of osteogenic gene expression indicated that the 10% LyPRP/Col І composite hydrogel could facilitate the early expression of BMP-2 and late osteogenic associated protein formation with higher expression of alkaline phosphatase and Osteocalcin (OCN). These results might provide new insights for the clinical application of 10% LyPRP/Col І composite hydrogel as practical bone repair injection.